Działania public relations wobec procesów globalizacji - Kulig-Moskwa, Katarzyna (Public relations and globalization, 2005)
The article presents the measures of globalization and the involvement of public relations. People's awareness have undergone changes, the need for ethics has increased, the identity of local companies has been questioned. Consequently, there are problems connected with the management of multinational companies. All these factors prompt companies to present and assist public relations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 38-48